The path to genocide in Rwanda : security, opportunity, and authority in an ethnocratic state - McDoom, Omar Shahabudin, 1973- (Cambridge : Cambridge University Press, 2021)
"The shocking characteristics of Rwanda's genocide in 1994 have etched themselves indelibly on the global conscience. The Path to Genocide in Rwanda combines extensive, original field data with some of the best existing evidence to evaluate the myriad theories behind the genocide and to offer a rigorous and comprehensive explanation of how and why it occurred, and why so many Rwandans participated in it. Drawing on interviews with over three hundred Rwandans, Omar Shahabudin McDoom systematically compares those who participated in the violence against those who did not. He contrasts communities that experienced violence early with communities where violence began late, as well as communities where violence was limited with communities where it was massive. His findings offer new perspectives on some of the most troubling questions concerning the genocide, while also providing a broader engagement with key theoretical debates in the study of genocides and ethnic conflict"--
Includes bibliographical references (pages 389-406) and index.
Keywords: Genocide -- Rwanda; Hutu (African people) -- Rwanda -- Politics and government; Tutsi (African people) -- Crimes against -- Rwanda; Rwanda -- Ethnic relations